Over-expression of a subgroup 4 R2R3 type MYB transcription factor gene from Leucaena leucocephala reduces lignin content in transgenic tobacco - Omer, Sumita; Kumar, Santosh; Khan, Bashir Mohammad (Plant Cell Reports, 2013)
LlMYB1 , a subgroup 4 R2R3-type MYB transcription factor gene from Leucaena leucocephala appears to be a repressor of lignin biosynthesis pathway by regulating the transcription of general phenylpropanoid pathway genes. R2R3MYB transcription factors are known to play a wide role in regulating the phenylpropanoid pathway in plants. In this study, we report isolation, cloning and characterization of an R2R3MYB transcription factor gene (LlMYB1) from an economically important tree species, Leucaena leucocephala. LlMYB1 consists of 705 bp coding sequence corresponding to 235 amino acids. Sequence alignment revealed that the N-terminal (MYB) domain of the gene shares up to 95 % similarity with subgroup 4 (Sg4) members of R2R3Myb gene family functionally known to be lignin repressors. Highly divergent C-terminal region of the gene carried an ERF-associated amphiphilic repression (EAR) motif, another characteristic of the Sg4. The gene was phylogenetically grouped closest with AmMYB308, a known repressor of monolignol biosynthetic pathway genes. Spatio-temporal expression studies at different ages of seedlings using quantitative real-time PCR (QRT-PCR) showed highest transcript level of the gene in 10 day old stem tissues. Over-expression of the gene in transgenic tobacco showed statistically significant decline in the transcript levels of the general phenylpropanoid pathway genes and reduction in lignin content. Our study suggests that LlMYB1 might be playing the role of a repressor of lignin biosynthesis in L. leucocephala.
Keywords: Leucaena leucocephala; lignin; R2R3MYB; Repressor; Transcript level